Houston, we still have a problem - Buchheit, M. (International Journal of Sports Physiology and Performance, 2017)
Apollo 13 was initially looking like it would be the smoothest flight ever. After the explosion of an oxygen tank, however, the astronauts were close to spending the rest of their lives in rotation around the planet. This well-known incident is used to further discuss the link, or lack thereof, between sport-science research and current field practices. There is a feeling that the academic culture and its publishing requirements have created a bit of an Apollo 13-like orbiting world (eg, journals and conferences) that is mostly disconnected from the reality of elite performance. The author discusses how poor research discredits our profession and provides some examples from the field where the research does not apply. In fact, the reality is that sport scientists often do not have the right answers. Some perspectives to improve translation are finally discussed, including a rethink of the overall publishing process: promotion of relevant submission types (eg, short-paper format, short reports, as provided by IJSPP), improvement of the review process (faster turnaround, reviewers identified to increase accountability, and, in turn, review quality), and media types (eg, free downloads, simplified versions published in coaching journals, book chapters, infographics, dissemination via social media). When it comes to guiding practitioners and athletes, instead of using an evidence-based approach, we should rather promote an "evidence-led" or "informed-practice" approach—one that appreciates context over simple scientific conclusions.